The moderating effect of emotion regulation on telecommuting intensity, anxiety and depression: A study on telecommuting in the Philippines - Golloso, Cecille Nicole Q. (Animo Repository, 2021)
Telecommuting is a work arrangement that has been growing in global popularity. To further understand the experiences of telecommuting in the Philippines, the present study examined the relationship between telecommuting intensity and mental health, particularly the tendency to develop symptoms of anxiety and depression, when moderated by the emotion regulation strategies of cognitive reappraisal and expressive suppression. A total of 202 individuals currently employed in the Philippines and are either working onsite or remotely participated in the study. The findings show that telecommuting intensity was not a significant predictor of anxiety and depression regardless of the level of cognitive appraisal or expressive suppression. The study also revealed that expressive suppression and age has a significant positive influence on anxiety and depression. Keywords: Telecommuting intensity, emotion regulation, cognitive reappraisal, expressive suppression, anxiety, depression